Peran Indonesia dalam Keketuaan ASEAN 2023: Perspektif Konstruktivisme - Sinta Julina (Jurnal Alternatif - Jurnal Ilmu Hubungan Internasional, 2023)
The research background is that in the era of a world full of challenges due to the Covid-19 pandemic, Indonesia is optimistic about taking on the duties of the 2023 ASEAN Chair. As Chair of ASEAN 2023, Indonesia certainly has an important role. Therefore, the author is interested in examining Indonesia 's role in the 2023 ASEAN Chair using a Constructivism Perspective. The purpose of this study is to examine and explain Indonesia's role in the 2023 ASEAN Chair using a Constructivism Perspective. To apply the research results, the authors use a descriptive research type. Data collection methods are document-based methods (document-based research) or internet-based methods (internet-based research). In this document-based or internet-based study, data and information are collected and analyzed to understand the phenomenon being studied. The data analysis method is qualitative. Based on the analysis, the results of the study show that the Constructivism Perspective identifies Indonesia's role in the Chair of ASEAN 2023 as a strategic role as a motor for peace, prosperity, regional architectural leaders by incorporating factors or elements of identity, understanding regarding collective identity and the interests of ASEAN not only the interests of Indonesia, providing benefits to regional and global community and make the ASEAN region a world's engine of sustainable growth.